Q&A: The Power of Distribution. - Hoffmann, Leah (Communications of the ACM, 2013)
An interview is presented with Nancy Lynch, a professor at the Massachusetts Institute of Technology. Topics include her career in computer science at institutions such as the University of Southern California, the 1985 FLP impossibility proof for distributed computing, the design and development of algorithms, the computer scientist Michael Fischer, and synchronous systems.